MEMAHAMI HADIS TENTANG KEPEMIMPINAN LAKI-LAKI ATAS PEREMPUAN DALAM KONTEKS KE-INDONESIAAN - Kholis (Kopertais Wilayah III Yogyakarta, 2022)
In general, humans are divided into two natures, that are man and woman. Both are outlined to complement each other but in fact, the relationship between the two often causes polemics when understanding the relationship between superior and inferior systems. This understanding has a basis in the texts of the Qur'an and the hadith of the Prophet Muhammad SAW. Even with the pretext of the arguments of the Qur'an, women often get legitimacy from men. Al-Quran and Hadith as socio-religious guidelines uphold human values. If we look at the historical context of the text, it can be concluded that the relationship that is built between men and women is not a superior coordinating relationship but a functional and moral cooperative. By using the takhrij-descriptive analysis method, this paper reviews the hadith about male leadership in the household which has been understood as a superior coordinative relationship. In fact, leadership in the household as well as the division of private and public tasks is based on the values ​​of responsibility and cooperative nature, and without any element of coercion in choosing the division of tasks. This is a moral idea to be built from the texts of the Qur'an and hadith. To actualize social life in Indonesia, this article uses Fazlur Rahman's opinion in understanding the leadership text. Keywords: Leadership, hadith, context, men, women, private, and public.